Commodity prices: a source book and index - Wasserman, Paul.; Kemmerling, Diane; Special Libraries Association (Detroit: Gale Research Co, 1974)
This book is a guide to commodity prices. This is an updated and thorough revision of Sources of commodity prices, published in 1959 as a project of the Business and Finance Division of the Special Libraries Association.
uaa 22/01/19
Loans.
Keywords: Prices; Primary commodities; Raw materials